Practical Guidelines on Implementing Hypofractionated Radiotherapy for Prostate Cancer in Africa - Swanson, William; Samba, Richard Ndi; Lavelle, Michael; Elzawawy, Ahmed; Sajo, Erno; Ngwa, Wilfred; Incrocci, Luca (Frontiers in Oncology, 2021)
Among a growing body of literature in global oncology, several articles project increased cost savings and radiotherapy access by adopting hypofractionated radiotherapy (HFRT) in low- and middle- income countries (LMICs) like those in Africa. Clinical trials in Europe and the USA have demonstrated HFRT to be non-inferior to conventional radiotherapy for eligible patients with several cancers, including prostate cancer. This could be a highly recommended option to battle a severely large and growing cancer burden in resource-limited regions. However, a level of implementation research may be needed in limited resource-settings like in Africa. In this article, we present a list of evidence-based recommendations to practice HFRT on eligible prostate cancer patients. As literature on HFRT is still developing, these guidelines were compiled from review of several clinical trials and professionally accredited material with minimal resource requirements in mind. HFRT guidelines presented here include patient eligibility, prescription dose schedules, treatment planning and delivery techniques, and quality assurance procedures. The article provides recommendations for both moderately hypofractionated (2.4-3.4Gy per fraction) and ultrahypofractionated (5Gy or more per fraction) radiation therapy when administered by 3D-Conformal Radiotherapy, Intensity Modulated Radiation Therapy, or Image-Guided Radiotherapy. In each case radiation oncology health professionals must make the ultimate judgment to ensure safety as more LMIC centers adopt HFRT to combat the growing scourge of cancer.